RELEVANSI LAHJAH DALAM KODIFIKASI QIRA’AT AL-QUR’AN PADA MASA KHALIFAH UTSMAN BIN ‘AFFAN - Ramdani, Mumammad; Izhar, Muhammad; Rizal, Rizal; Dasuki, Ahmad (Yayasan Panca Bakti Wiyata Pangandaran, 2025)
This research aims to examine the relevance of dialects in the codification of Quranic recitation during the era of Caliph Uthman bin Affan. The methodology employed involves data collection through literature review and critical analysis of the Quranic text and various recitations, utilizing historical and linguistic approaches. The primary focus is on how the dialectal variations prevalent among Arab society influenced the establishment of a standard Mushaf (scripture), aiming to prevent fragmentation caused by diverse recitation practices. The research findings indicate that dialectal variations played a crucial role in the development and establishment of the official Quranic recitation, not only preserving textual unity but also strengthening social integration and religious understanding among Muslims. The codification process undertaken by Caliph Uthman proved a strategic step in responding to the dynamics of a multilingual and multicultural society, thus establishing stability in religious practice. Furthermore, Qira'at (recitation styles), as an orally transmitted tradition, reflects the rich culture of the Muslim community and serves as an effective means of preserving the originality of Quranic recitation. These findings highlight the importance of linguistic and sociological approaches in understanding the historical and social dynamics behind the codification of Qira'at and its implications for contemporary Islamic education. This research provides new insights into the relationship between language and religion, and emphasizes the need to preserve the tradition of Qira'at within the context of cultural diversity and the challenges of globalization.